Reflecting on “Issues Supervising Family Violence Cases” - Keats, Patrice A. (Canadian Journal of Counselling and Psychotherapy, 2010)
In reflecting on Dawn McBride’s article entitled Issues Supervising Family Violence Cases, I use a case study to confirm and add to McBride’s ideas. Specifically, areas of focus include advocacy and social influence with disabled clients, dangers for counsellors related to violent partners or family members, additional issues about agency documentation and confidentiality, cultural aspects of family violence in relation to immigrants, and attending to mental illness and vulnerability to violence. Finally, McBride includes a handout covering areas that would initiate supervision for counsellors involved with this population; strong support for its distribution is advocated.